Standards Australia. - Standards Australia (Sydney : Standards Australia)
"Standards Australia is the nation's peak non-government, not-for-profit Standards organisation. Our expertise and main responsibility is the development and adoption of standards in Australia. We also facilitate Australian participation in international standards development. We do not enforce, regulate or certify compliance with these standards. We form technical committees by bringing together relevant parties and stakeholders. Through a process of consensus, these committees develop standards for Australia's net benefit. The work of Standards Australia enhances the nation's economic efficiency, international competitiveness and contributes to community demand for a safe and sustainable environment."--About us
Title from title screen (viewed on 15 May 2017)
Mode of access: Available Online. Address as at 23/05/2017
Selected for archiving
Keywords: Manufactures -- Standards -- Australia; Standardization -- Australia; Standards, Engineering -- Australia; Australian